The Role of Digital Technology in Integrating Strategic Planning and Budgeting: A Literature Review - Usman, Asri; Mediaty, Mediaty; Anggraeni, Ayu Dhina; Nusa, Gratia Triyana; Anugrah, Nurhikma Dewi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the role of digital technology in strengthening the link between strategic planning and budgeting as an effort to improve the effectiveness of organizational management in the era of digital transformation. This study focuses on how digitalization, through various technological innovations, can integrate strategic planning processes with budgeting in an adaptive and efficient manner. This study used the Systematic Literature Review (SLR) method with the aim of compiling the literature in a structured manner and identifying the contribution of digital technology to the integration of strategic planning and budgeting. Data collection was conducted through searching scientific articles, journals, conference proceedings, and other relevant academic sources using the Scopus, ScienceDirect, Emerald Insight, Elsevier, and Google Scholar databases. Keywords used included strategic planning, budgeting, digitalization, ERP, e-budgeting, and business analytics. A total of 25 articles published between 2019–2024 were selected based on inclusion criteria such as topic suitability, English or Indonesian language, and availability of full access. The study shows that the implementation of digital technologies such as Enterprise Resource Planning (ERP), Business Intelligence (BI), big data analytics, and cloud-based systems plays a significant role in improving accuracy, transparency, flexibility, and real-time data-driven decision-making. Integrating digitalization between strategy and budget also helps organizations adapt to changes in the business environment quickly and efficiently. However, implementation effectiveness is greatly influenced by the readiness of digital infrastructure, human resource competency, and organizational culture. This research provides implications for managers and policy makers to make digitalization an integral part of strategic planning and budgeting, with the support of technology training and strengthening of management information systems.